KERUSAKAN TEGAKAN TINGGAL AKIBAT KEGIATAN PENEBANGAN DAN PENYARADAN: KASUS DI SUATU PERUSAHAAN HUTAN DI RIAU - Sona Suhartana; Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
This paper presents study results of residual stand damages caused by felling and skidding activities. The case study was carried out at PT Dwi Marta in Riau in 1993. The aims are : (1) tofind the impact of felling and skidding on residual stand damages, (2) to know the factors influencing the residual stand damages and (3) tofind the way of reducing residual stand damage.Data on the number of trees with diameter 20 cm and up, trees damages were collected. The data was analised by using themultiple regression.The result of study shows :1.The residuol stand damage caused by felling ranged between 2.7-10. 6% with an average of 6.6%/ha.2.The residual stand damage caused by skidding with crawler tractor varied from 2. 7% to 22.3% with an average of 12. 7%ha.3.Both the number of trees felled and the slope in had highly significant effect to residual stand damages. The greater the number of trees felled and the slope, the greater the residual stand damages.